ANALISIS TINGKAT KECEMASAN AKADEMIK PESERTA DIDIK KELAS V DALAM MENGHADAPI ASESMEN SUMATIF DI SDIT ATIKAH MUSADDAD AL-WASILAH GARUT - Permata Sari, Indah; Maulida Aulia Rahman; Muhammad Nurjamaludin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of academic anxiety of fifth-grade students facing summative assessments at SDIT Atikah Musaddad Al-Wasilah Garut in the 2024/2025 academic year. Academic anxiety is understood as a psychological condition that arises when students face academic demands in the form of exams or tests, characterized by fear, worry, and emotional stress. This study used a quantitative approach with a descriptive survey method. The instrument used was an academic anxiety questionnaire compiled based on physical, cognitive, and behavioral aspects. Data analysis was carried out through validity, reliability, normality tests, and descriptive analysis with the help of SPSS version 27 software. The results showed that the level of academic anxiety of students was in the fairly high category, with a distribution of 20% in the low category, 50% in the moderate category, and 30% in the high category. The dominant symptoms experienced by students included difficulty concentrating, excessive nervousness during exams, worry about getting low grades, and pressure due to parental and teacher expectations. These findings indicate that academic anxiety has the potential to affect the learning process, reduce self-confidence, and impact assessment results. Therefore, intervention strategies are needed that involve teachers, schools, and parents in helping students manage their academic anxiety more effectively.